The β2‐Adrenoceptor Agonist Terbutaline Stimulates Angiogenesis via Akt and ERK Signaling. Issue 2 (20th July 2016) - Lemmens, Stefanie; Kusters, Lauren; Bronckaers, Annelies; Geurts, Nathalie; Hendrix, Sven
Abstract : Angiogenesis is associated with changes in endothelial cell (EC) proliferation and tube formation, controlled by extracellular receptor‐activated kinase (ERK)/mitogen activated protein kinase (MAPK) and Akt signaling. Important regulators of these systems include hormones acting on G‐protein‐coupled receptors, such as beta 2‐adrenoceptors (β2‐ARs). In central nervous system (CNS) trauma, the importance of β2‐AR modulation has been highlighted, although the effects on revascularization remain unclear. Vascular protection and revascularization are, however, key to support regeneration. We have investigated the angiogenic capacity of the specific β2‐AR agonist terbutaline on ECs derived from the CNS, namely bEnd.3‐cells. As angiogenesis is a multistep process involving increased proliferation and tube formation of ECs, we investigated the effects of terbutaline on these processes. We show that terbutaline significantly induced bEnd.3 tube formation in a matrigel in vitro assay. Moreover, administration of specific inhibitors of ERK and Akt signaling both inhibited terbutaline‐induced tube formation. The proliferation rate of the ECs was not affected. In order to investigate the general effects of terbutaline in an organotypic system, we have used the chick chorioallantoic membrane (CAM)‐assay. Most importantly, terbutaline increased the number of blood vessels in this in ovo setting. Although we observed a positive trend, the systemic administration of terbutaline did not significantly improve the functional outcome, nor did it affect revascularization in our spinal cord injury model. In conclusion, these data indicate that terbutaline is promising to stimulate blood vessel formation, underscoring the importance of further research into the angiotherapeutic relevance of terbutaline and β2‐AR signaling after CNS‐trauma. J. Cell. Physiol. 232: 298–308, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Terbutaline is a promising beta 2‐adrenoceptor agonist to stimulate blood vessel formation. It significantly promotes tube formation by mouse brain endothelial cells. Most importantly, it increases the number of blood vessels in the organotypic setting of the chorio‐allantoic membrane assay.